2020
DOI: 10.3390/cli8100102
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Climate Change on the Water Resources of the Kunduz River Basin, Afghanistan

Abstract: The Kunduz River is one of the main tributaries of the Amu Darya Basin in North Afghanistan. Many communities live in the Kunduz River Basin (KRB), and its water resources have been the basis of their livelihoods for many generations. This study investigates climate change impacts on the KRB catchment. Rare station data are, for the first time, used to analyze systematic trends in temperature, precipitation, and river discharge over the past few decades, while using Mann–Kendall and Theil–Sen trend statistics.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…In a study from Tibetan Plateau, Wang et al (2008) reported increased warming at the rate of 0.36 °C per decade by analyzing data from 90 weather stations. In the Himalayan region, maximum increase in temperature (1.45-1.8 °C) was reported for Afghanistan (Aich et al, 2017;Kamiabinia et al, 2017;Akhundzadah et al, 2020; Table 1). Based on regional climate models, it was predicted that the temperature in the Indian subcontinent will rise between 3.5 and 5.5 °C by 2100, and on the Tibetan Plateau by 2.5 °C by 2050 and 5 °C by 2100 (Kumar et al, 2006).…”
Section: Trends Of Climatic Parameters In the Himalayamentioning
confidence: 90%
“…In a study from Tibetan Plateau, Wang et al (2008) reported increased warming at the rate of 0.36 °C per decade by analyzing data from 90 weather stations. In the Himalayan region, maximum increase in temperature (1.45-1.8 °C) was reported for Afghanistan (Aich et al, 2017;Kamiabinia et al, 2017;Akhundzadah et al, 2020; Table 1). Based on regional climate models, it was predicted that the temperature in the Indian subcontinent will rise between 3.5 and 5.5 °C by 2100, and on the Tibetan Plateau by 2.5 °C by 2050 and 5 °C by 2100 (Kumar et al, 2006).…”
Section: Trends Of Climatic Parameters In the Himalayamentioning
confidence: 90%
“…The population living in this basin was reported to be about 4.5 million people in 2015. According to the division of the Ministry of Energy and Water, it is divided into 7 sub-basins: Upper Five, Lower Five, Kokcheh, Taloqan, Upper Kunduz, Lower Kunduz, and Lower Amu [28,33].…”
Section: Study Areamentioning
confidence: 99%
“…The vegetation in Afghanistan has been severely affected by human activities, climate change, and drought, which resulted in the naturally occurring vegetation preserved intact only in a few high mountain areas and abnormally dry deserts [27]. Such a situation additionally contributes to Afghanistan's vulnerability to the effects of climate change [28]. In Afghanistan, the combined effects of climate change and four decades of civil war have destroyed vegetation and infrastructure, leading to the underdevelopment of the country.…”
Section: Introductionmentioning
confidence: 99%
“…The vegetation in Afghanistan has been severely affected by human activities, climate change, and drought, which resulted in the naturally occurring vegetation preserved intact only in a few high mountain areas and abnormally dry deserts (Rousta et al 2020a). Such a situation additionally contributes to Afghanistan's vulnerability to the effects of climate change (Akhundzadah et al 2020). In Afghanistan, the combined effects of climate change and four decades of civil war have destroyed vegetation and infrastructure, leading to the underdevelopment of the country.…”
Section: Introductionmentioning
confidence: 99%